THE IMPACT OF STRATEGIES APPLIED BY THE UAE CYBERSECURITY COUNCIL AGAINST CYBERSECURITY THREATS WITHIN THE UAE GOVERNMENT ORGANIZATION AND ENTITIES (Lex localis - Journal of Local Self-Government, 2025)
Considering the increasing cybercrimes in the world and in the UAE, this study has been designed to explore the factors that have the potential to significantly control cybercrimes. The researcher conducted detailed literature review for identifying the factors and the laws that the government has made for the control of cybercrimes. Using the theoretical support of technology acceptance model, the framework of the study has been developed to cover the four key factors that have the potential to control cybercrimes. The data has been analyzed using SMART PLS 3. The findings revealed that all the variables have a significant positive impact over cyber security. The study ends up with theoretical and practical contributions along with highlighting the limitations of the current research and avenues for the future studies.